Cytogenetic characterization of the strongly electric Amazonian eel, Electrophorus electricus (Teleostei, Gymnotiformes), from the Brazilian rivers Amazon and Araguaia - Fonteles, Soraia B.A.; Lopes, Carlos E.; Akama, Alberto; Fernandes, Flora M.C.; Porto-Foresti, Fábio [UNESP]; Senhorini, José A.; Daniel-Silva, Maria de Fátima Z.; Foresti, Fausto [UNESP]; Almeida-Toledo, Lurdes Foresti de (Sociedade Brasileira de Genética, 2008)
A karyotype analysis of the electric eel, Electrophorus electricus (Teleostei, Gymnotiformes), a strongly electric fish from northern South America, is presented. Two female specimens were analyzed, one from the Amazon River and one from the Araguaia River. The specimens had a chromosomal number of 2n = 52 (42M-SM + 10A). C-bands were present in a centromeric and pericentromeric position on part of the chromosomes; some interstitial C-bands were also present. Heteromorphic nucleolus organizer regions (NORs) were detected in two chromosome pairs of the specimen from the Amazon River. The chromosome number and karyotype characteristics are similar to those of other Gymnotidae species. The genera Electrophorus and Gymnotus are positioned as the basal lineages in the Gymnotiformes phylogeny.
Keywords: chromosome; fish; Gymnotidae; electric eel